The Rate of General and Managerial Educations among Managers and Chief Experts in Iran Universities of Medical Sciences/ Vice Chancellors for Health - Mohammad Esmaeil Motlagh; Seyed Davoud Nasrollah pour Shirvani; Mohamad Reza Maleki; Shahram Tofighi; Mohammad Javad Kabir; Nahid Jafari (Kerman University of Medical Sciences, 2012)
Background & Objective : Education and improvement of human resources is a kind of investment in organizations and have a key role in improving their performance and productivity This study was conducted to determine the rate of managerial trainings among managers and chief experts in health deputies of Iran Medical Sciences Universities and its relation to demographic and institutional factors Methods: This crosssectional study was conducted in spring 2011 Sample population was managers and experts of Health Deputies of Medical Sciences Universities in Iran Thirteen universities were selected by random systematic and stratified sampling and their managers and chief experts were interviewed by using a questionnaire consisted of demographic and organizational variables as well as 40 managementrelated topics Results: A total of 293 managers and chief experts were studied Among 40 studied management topics only in 8 topics over than 40% had been trained and in 32 remained topics the rate of trained individuals varied from 1% to 40% The rate of education showed significant relationship with the grade of university and subjects sex age work experience educational level and field taking MPH courses and current work location and position (p